Manajemen Perpajakan dan Analisa Deteksi Dini terhadap Tax Evasion Melalui Metode Benchmark - M. Khoiru Rusydi; Alfiah Kusumawati (Jurnal Aplikasi Manajemen, 2012)
The purposes of this research applaied tax management andidentifying tax evasion practice using total benchmarking ratio analysis. Benchmark Ratio was settled by Dirjen Pajak based on industrial classification. Rate-payer ratio was counted based on company’s financial report. The reseach used the qualitative method. The research is using secondary financial data from cigarate industry. The result of the research concludes that rate-payer ratio was compared with the benchmark, fittingness rate of the company’s ratio showed through the ratio’s difference between Rate-payer and the benchmark. The difference that was too low or too high used as an inspection basis. The present of false recorded amount was a proof that tax evation was happened in the company. The tax liability in fact could be traced dan calculated through supporting financial report evidence. Tax evasion can be avoided by applying a proper tax planning. Also by considering gap in the Tax Law, rate-payer is possible applying deductable expenses strategy without doing tax evasion.Keywords: Tax evasion, Financial report, Benchmark ratio, Tax planning